Francis J. Carmody: the Manx recordings - Carmody, Francis J. (Studia Celtica, 2018)
During July 1949 Francis J. Carmody (1907-82), Professor of French in the University of Calfornia at Berkeley, visited the Isle of Man and obtained Manx Gaelic material from six of the remaining native Manx speakers. In looking through Carmody's material it is clear that in a - number of places he has proposed either an inaccurate translation for the text in hand or has not fully understood what was said to him by the speaker concerned. Whilst Wagner (July 1950) and Jackson (Christmas / New Year 1950-1) organised their material to reflect Late Manx syntax and - phonology respectively, Carmody concentrates on its morphology, organising sentences to elicit the particular aspect of the morphology sought. In spite of some shortcomings, given that Carmody's is the only body of material, though small, which looks at Late Manx morphology, I still consider - it worthwhile to make Carmody's material once more available and to bring his transcriptions up to date with current IPA script and integrate them into the main corpus of recorded Manx speech, thereby bringing them into line with those of Rhŷs and Marstrander, Wagner and Jackson, as - well as that of the sound-recorded material, thus completing the collection. From the same people, as well as two non-native speakers, he made some four hours of tape recordings, believed to be housed in the above university.